The importance of family, leisure, work, and friends - Ross Barker; Isabella Buber-Ennser; Yen Thi Hai Nguyen; Maria Rita Testa (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2023)
In this paper, we investigate the importance of various aspects of life-that is, the value of family, leisure, work, and friends distinguished by age and parenthood. Our data is from the European Values Study and World Values Survey, capturing 46 countries in Europe, East Asia, Latin America and Australia. We focus on persons in young and middle adulthood and examine the perceived importance of the four life domains in 2005-2009 and 2017-2019 and the changes over the roughly 10- year period. Our results show that family is most often regarded as important, followed by work, friends, and leisure. This hiearchary remained the same during the last decade. The descriptive results show an increase in the importance of family, friends, and leisure, with significant regional differences. Regionally, Southern Europe and East Asia have the most significant changes in values over the 10-year period. Differentiations by age and parity reveal that the associations of age and parity are weaker in 2017-2019 than in 2005-2009.
Keywords: 300; Importance of life domains; family; leisure; work; friends; European Values Study (EVS); World Values Study (WVS)